P588 Interim results from the randomised VERDICT trial to determine the optimal treatment target in patients with ulcerative colitis. (30th January 2023) - Jairath, V; Zou, G; Wang, Z; Adsul, S; Colombel, J F; D'Haens, G R; Freire, M; Moran, G W; Peyrin-Biroulet, L; Sandborn, W J; Sebastian, S; Travis, S; et al.
Abstract: Background: The optimal treatment target for ulcerative colitis (UC) is uncertain. The VERDICT trial in moderate to severe UC aims to determine if a treatment target of corticosteroid (CS)-free symptomatic + endoscopic + histologic remission is superior to CS-free symptomatic remission alone. Trial progress and the study cohort to date are described herein. Methods: Our aim is to enrol 660 patients with moderately to severely active UC (Mayo rectal bleeding subscore [RBS] ≥1; Mayo endoscopic score [MES] ≥2). Patients are randomised to 3 treatment targets (2:3:5 ratio): CS-free symptomatic remission (Mayo RBS = 0) (Group 1); CS-free endoscopic remission (MES ≤1) + symptomatic remission (Group 2); or CS-free histologic remission (Geboes score <2B.0) + endoscopic + symptomatic remission (Group 3). Therapy is administered according to a treatment algorithm that is dependent upon each patient's UC treatment at screening. Early introduction of vedolizumab (VDZ) and dose escalation up to 300 mg every 4 weeks until the target is met are central to each algorithm. Up to 3 opportunities to achieve the assigned target were prespecified in the algorithms (weeks 16, 32, or 48). Patients and central readers for endoscopy/histopathology are blinded to group allocation, and investigators are unblinded. Results: As of 2 November 2022, 331 patients were enrolled at 55 sites across 10 North American and European countries. Mean (SD) baseline characteristics (Table) include a UC duration of 8.6 (8.3) years, Mayo Clinic score of 8.7 (1.7), C-reactive protein level of 13.3 (15.6) mg/dL, and a faecal calprotectin level of 1462.3 (1481.3) mg/kg. At baseline, 52% (172/331) and 11% (37/331) of patients were receiving concomitant CS and immunosuppressives, respectively, and 14% (47/331) had current/prior exposure to tumour necrosis factor antagonists. Most patients (85%) were receiving nonbiologic therapy. Of all randomised patients, 43/69 (Group 1), 65/98 (Group 2), and 115/164 patients (Group 3) have reached week 16; and 28 (65%), 25 (39%), and 42 (37%) met their target, respectively. After a median of 35 weeks (IQR 18-53), a total of 30 (Group 1), 32 (Group 2), and 50 patients (Group 3) have met their target and will be followed to relapse or study termination. The serious adverse event rate (8%; 36/483) was similar across groups. Conclusion: VERDICT has randomised ~50% of its target enrolment. Enrolled patients represent a typical moderate to severe UC population and are primarily bionaive and receiving early VDZ initiation. Early results suggest the feasibility of achieving each treatment target, specifically histologic remission, and are consistent with expected values. No new VDZ safety signals were identified. Completion of enrolment is anticipated in late 2023.